Prediction of Online Customer Satisfaction: A Case Study Go-Ride in Jabodetabek - Rissa Hanny; Fahrizal (Universitas Warmadewa, 2021)
The increasing number of online motorcycle taxis has an impact on tighter competition. PT Gojek Indonesia, which has existed since 2010, provides online motorcycle taxi transportation services based on applications under the 'GoJek' brand. This research examines how online customer satisfaction predicts service quality and brand image of Go-Ride services in the Jabodetabek area and the influence of both. This variety of causation studies serving as explanations and using the quantitative approach. Populations are passengers of Go-Ride services, located at Pasaraya Blok M, South Jakarta, that comes from that consumer in Jabodetabek area. The research sample uses purposive sampling to customer used Go-Ride's services as the counting of 96 respondents. Regression analysis technique using multiple regression. The results prove that online customer satisfaction can predict the service quality and brand image factors as Go-Ride's services yield impact partially and simultaneously. This is also reinforced by online customer satisfaction contributing 55.2 percent to predict service quality and brand image in this research.